Higher Rate of Intracerebral Hemorrhage in Hispanic Patients with Cerebral Cavernous Malformation - Jenson, Amanda V. (J Vasc Interv Neurol, 2015)
Cerebral cavernous malformations (CCM) are vascular malformations prone to intracerebral hemorrhage and epilepsy. Studies about the natural history and clinical presentation in the Hispanic population are lacking [7]. Retrospectively, we identified demographics and clinical features of Hispanic patients with CCM in our neurology clinic. Comparison with studies in the non-Hispanic White population with CCM was conducted. RESULTS: A total of 15 Hispanic patients diagnosed with CCM were identified in our neurology clinic. The majority of our patients presented with symptomatic hemorrhage (27%, n = 4) or seizure(s) (47%, n = 7). Of 15 patients, there were a total of four patients (27%) that had recurrent hemorrhages with an annual rate of recurrent hemorrhage of 8.04%. Our cohort had a higher rate of intracerebral hemorrhage after any initial mode of presentation (47%, n = 7) compared with non-Hispanic White population studies: 11% (n = 32) and 4% (n = 5). (p < 0.05) CONCLUSIONS: Hispanic patients with CCM have a higher rate of hemorrhage during follow-up after any presentation of CCM (p<0.05) when compared to CCM in the non-Hispanic White population.